ANALYSIS OF NATIONAL AND FOREIGN EXPERIMENTS ON THE DIAGNOSIS OF PROCESSES FOR THE DEVELOPMENT OF A SENSE OF PATRIOTISM - Kuvondikov Sardorkhon Sidikovich (Journals Park Publishing, 2023)
This article was used as an indicator of the assessment of upbringing when introducing the "concept of continuous spiritual education" from the criteria and indicators of the development of civil and Patriotic competence of future teachers. As a result, the ability to diagnose the readiness of future teachers to form students ' loyalty to the Motherland has increased. The interactive forms, methods and tools developed in the framework of the study, based on the competence-based approach of developing a sense of patriotism, were used in the development of the educational manual "pedagogical science and technology of education". These proposals made it possible to prepare future teachers for educational activities, to develop an active civil position in them.
Keywords: Patriotic consciousness, Patriotic Outlook, moral, civil-Patriotic, military-Patriotic, sports-Patriotic, pedagogy, future teachers, educational activities, education, upbringing, competence, modernization.